Enhancing Counseling Practices with Total Quality Management and Photovoice to Mitigate Academic Burnout in Madrasah - Syamsuddin, Riswani; Zarkasih, Zarkasih; Munawwaroh, Lailatul; Salman, Nola Fibriyani Bte (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Academic burnout among madrasah students remains insufficiently examined, especially through participatory and culturally responsive approaches. Existing research tends to emphasize quantitative measurement or teacher-centered interventions. This study seeks to address this gap by integrating photovoice within a Participatory Action Research (PAR) framework and grounding it in the principles of Total Quality Management (TQM) to explore and mitigate academic burnout. The research involved collaboration with two Guidance and Counseling teachers and ten students at a Madrasah Tsanawiyah in Pekanbaru. Data were collected through reflective writing, semi-structured interviews, photo elicitation, and participatory observation, and analyzed using thematic coding with methodological triangulation. The findings demonstrate that photovoice effectively exposes latent academic stress, strengthens teachers’ reflective practice, and promotes meaningful student engagement in counseling processes. Visual narratives—such as torn notebooks, clocks, and fatigue-related imagery—functioned as symbolic expressions of burnout that facilitated empathetic dialogue and informed more precise intervention strategies. This study contributes a novel model of student-led visual diagnostic practice within Islamic school counseling, aligned with TQM’s continuous improvement framework. The findings highlight the value of photovoice as a culturally relevant and sustainable method for strengthening student-centered burnout prevention and improving the overall quality of guidance and counseling services in madrasah settings.